The effect of Sure Start on youth misbehaviour, crime and contacts with children's social care - Pedro Carneiro; Sarah Cattan; Gabriella Conti; Claire Crawford; Elaine Drayton; Christine Farquharson; Nick Ridpath (Institute for Fiscal Studies (IFS), 2024)
This report studies the impact of Sure Start, which supported families of under-5s, on children's behaviour, youth offending and social care contacts.
Keywords: 330; Education and skills; Childcare and early years; Criminal justice; Early childhood development; Education; Family